2017
DOI: 10.1002/jemt.22980
|View full text |Cite
|
Sign up to set email alerts
|

A cone‐beam computed tomography study of the anatomical relationships between mandibular teeth and the mandibular canal, with a review of the current literature

Abstract: The purpose of this study was to evaluate age- and sex-related changes in the anatomical relationships between the roots of the molars and premolars and the mandibular canal using cone-beam computed tomography (CBCT) images. A total of 243 patients (116 males, 127 females) aged 16-83 years for whom previous CBCT scans were available were enrolled in this study. The patients were subcategorized by sex and age (Group I, <21 years; Group II, 21-40 years; and Group III, >40 years). The distances between the mandib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
38
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 29 publications
(65 reference statements)
10
38
1
3
Order By: Relevance
“…In the current study, we found that the distance from the root apices to the IAC increased, moving anteriorly from the distal root of the second molar to the mesial root of the first molar. This result is in agreement with that of Aksoy et al,22 who examined the proximity of mandibular teeth to the IAC and found that the second molar is significantly closer to the IAC compared to the first molar and premolars. They also found that the second molar is in direct contact with IAC in 16% of cases, whereas only 3.3% of the first molars were in contact with the IAC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, we found that the distance from the root apices to the IAC increased, moving anteriorly from the distal root of the second molar to the mesial root of the first molar. This result is in agreement with that of Aksoy et al,22 who examined the proximity of mandibular teeth to the IAC and found that the second molar is significantly closer to the IAC compared to the first molar and premolars. They also found that the second molar is in direct contact with IAC in 16% of cases, whereas only 3.3% of the first molars were in contact with the IAC.…”
Section: Discussionsupporting
confidence: 93%
“…This could possibly be explained by our sample age distribution, in which most of our subjects (45 subjects, 75%) were younger than 30 years. Previous studies have demonstrated that age affects the proximity of the IAC to the roots of the mandibular teeth, with younger patients having shorter distances between the teeth and IAC 14,22-24. An increase in this distance with age is likely due to the fact that the craniofacial complex continuously changes throughout life 22.…”
Section: Discussionmentioning
confidence: 97%
“…According to our data, the roots of 69 second molars (33.8% of the total number of the second molars) in 43 cases (20 women and 23 men) were radiographically in direct contact with the MC. The incidence was twice as high as the data given by Bürklein et al, 3 and Aksoy et al, 5 which showed the direct contact of roots with the canal in 15.2% and 16% of the second molars respectively. They considered that their investigation was the first study reporting the relatively high incidence of the direct contact between the root apices with the mandibular canal.…”
Section: Discussionmentioning
confidence: 50%
“…According to our data, the roots of 9.3% of the second premolars were in direct contact with the upper wall of the mandibular canal. Direct communication between second premolar and the MC was found in 3.2% of teeth by Bürklein et al, 3 and in 3.3% of teeth by Aksoy et al 5 Individual variations in the position of the mandibular canal relatively to the roots were assessed in the present study. The canal can be located below the roots, on the buccal or lingual side.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation